Fundamentals of digital communication - Madhow, Upamanyu (Cambridge University Press, 2008)
This textbook presents the fundamental concepts underlying the design of modern digital communication systems, which include the wireless, wireline, and storage systems that pervade our everyday lives. Using a highly accessible, lecture-style exposition, this rigorous textbook first establishes a firm grounding in classical concepts of modulation and demodulation, and then builds on these to introduce advanced concepts in synchronization, noncoherent communication, channel equalization, information theory, channel coding, and wireless communication. This up-to-date textbook covers turbo and LDPC codes in sufficient detail and clarity to enable hands-on implementation and performance evaluation, as well as "just enough" information theory to enable computation of performance benchmarks to compare them against. Other unique features include the use of complex baseband representation as a unifying framework for transceiver design and implementation; wireless link design for a number of modulation formats, including space-time communication; geometric insights into noncoherent communication and equalization. The presentation is self-contained, and the topics are selected so as to bring the reader to the cutting edge of digital communications research and development." "Numerous examples and end-of-chapter homework problems illustrate the key principles, with a view to allowing the reader to perform detailed computations and simulations based on the ideas presented in the text. The textbook is suitable for advanced undergraduate and graduate students of electrical and computer engineering, and can be used as the basis for a one- or two-semester course in digital communication. It will also be a valuable resource for practitioners in the communications industry.